Peningkatan Literasi Bisnis Digital Melalui Pelatihan Introduction To Digital Business Skills – HP Life Di SMK Negeri 3 Kota Bengkulu - Sabita Ramadhani; Herlina Herlina; Selly Anggraini; Ocy Lara Putri; Puja Lestari (Jurnal Dehasen Mengabdi, 2026)
Berbahasa Inggris This training program aims to enhance the digital business literacy of students at SMK Negeri 3 Kota Bengkulu, ensuring they possess essential competencies relevant to the job market and entrepreneurship in the digital era. The main challenge identified was the students' low understanding of utilizing digital platforms for business and promotional purposes. As a solution, the Introduction to Digital Business Skills Training was conducted using the structured curriculum from the HP Life (Hewlett-Packard Learning Initiative for Entrepreneurs) platform. The community service methodology involved three primary stages: 1) Planning (needs assessment and module adaptation), 2) Implementation (interactive material delivery, hands-on practice in registering HP Life accounts, and completion of core modules), and 3) Evaluation (measuring knowledge improvement through a post-test). The training, attended by 40 students from the Business and Marketing major, yielded positive results. The average evaluation score increased by 35% compared to the pre-test, indicating a significant enhancement in the comprehension of digital business concepts. The HP Life training is proven effective as a self-learning medium that can cultivate essential digital business skills among vocational high school students, thus better preparing them for the challenges of the digital economy.